Polarimetric method of plasma diagnostics. (1st September 2022) - Oganesyan, Koryun B; Dzierżęga, Krzysztof; Kopcansky, Peter; Gevorgyan, Ashot H; Timko, Milan
Abstract: The polarization plane rotation angle of a probe signal in plasma is calculated. The estimates of the residual gas average density and the average magnitude of the magnetic field in a cesium plasma based on the effects of Faraday and Cotton–Mouton in a probe laser field have been found. It is shown that the polarization plane rotation angle depends on resonance detuning of the incident laser wave and transition frequency of medium atoms, magnetic field strength and matrix element.